Questionnaire Development Process to Measure the SMEs' Continuous Use behavior towards Cloud Computing Services - Al-Sharafi, Mohammed A.; Ruzaini, Abdullah Arshah; Abu-Shanab, Emad A. (ACM Digital Library, 2019)
In the business world, cloud computing (CC) technologies are emerging computing platforms used to improve the deployment of ICT services with the aim of improving performance and competitive advantage. However, enough attention has not been given to the factors that influence the continuous use behavior of organizations towards CC services. Hence, this study aims to develop a reliable and valid questionnaire for the determination of the continuous use behavior of SMEs towards CC services. The questionnaire used in this study passed through three basic steps in accordance to the established scale development guidelines provided by Moore and Benbasat [1]. The questionnaire included three main sections with 87 questions. The questionnaire serves as a tool that will help SMEs and CC service providers to plan their strategies for providing a supportive sustained use of CC services in Malaysia.